2019
DOI: 10.3390/ani9060387
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Provides Novel Insights into Heat Stress Responses in Sheep

Abstract: With the intensified and large-scale development of sheep husbandry and global warming, sheep heat stress has become an increasingly important issue. However, little is known about the molecular mechanisms related to sheep responses to heat stress. In this study, transcriptomic analysis of liver tissues of sheep in the presence and absence of heat stress was conducted, with the goal of identifying genes and pathways related to regulation when under such stress. After a comparison with the sheep reference genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
(44 reference statements)
1
19
0
1
Order By: Relevance
“…It has also been found in other studies that different levels of feed nutrition can alter gene expression [28,29]. Secondly, grazing sheep, stimulated by hot summers and cold winters, can also change gene expression [30,31].…”
Section: Discussionmentioning
confidence: 68%
“…It has also been found in other studies that different levels of feed nutrition can alter gene expression [28,29]. Secondly, grazing sheep, stimulated by hot summers and cold winters, can also change gene expression [30,31].…”
Section: Discussionmentioning
confidence: 68%
“…Savitha et al [45] suggested a higher expression of TLR3, TLR3, TLR7, TLR8 and TLR9 as reliable immunological markers for the indication of the severity of heat stress in goats. Higher expression of interleukin type 1 receptors (IL1R1, IL1R2) and heat shock-related 70-kDa protein 2 (HSPA2) are also seen in heat-stressed sheep, suggesting that these genes also play an important role in the immunological responses [46].…”
Section: Thermoregulatory Mechanisms In Small Ruminantsmentioning
confidence: 99%
“…Heat stress could lead to enormous economic loss in rabbit industry by decreasing feed intake and increasing mortality rate [19,20]. Transcriptome studies have been widely used to explore the underlying molecular basis of heat resistance in animals, such as the cow [2], sheep [8], chicken [3], and duck [6]. In the current study, we artificially induced heat stress condition in rabbit, by which the global gene expression profiles have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, R 2 > 0.8 was considered suitable. For exploring gene expression profile in each sample, all the genes were categorized into five groups based on their FPKM values: very low expression gene (0-1), low expression gene (1-3), medium expression gene (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), high expression gene (15-60), and extremely high expression gene (>60).…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%